國民小學職前教師教學能力檢定評分量表建構之研究-以國立新竹教育大學教育學系為例 A Rating Scale for Assessing the Teaching Competency of Elementary School Preservice Teachers: A Study on the Department of Education at the National Hsinchu University of Education - 邱于閔 Yu- Min Chiu; 詹惠雪 Hui-Hsueh Chan (National Changhua University of Education, 2015)
本研究旨在編製「國民小學職前教師教學能力檢定評分量表」，作為國立新竹教育大學教育學系職前教師教學能力檢定之評量工具。本研究採德懷術研究法，自編「國民小學職前教師教學能力檢定評分量表」問卷，經17 位專家三回合德懷術資料分析，修正後形成評分量表。第二階段試用評分量表，參與試教對象為大四的職前教師，每次試用有8 位試教者及3 位評分人員，蒐集二次試教評分結果，以Kendall's W 和諧係數檢定進行評分者間信度考驗，並訪談試教者及評分人員進行指標修正。本研究結果提出之「國民小學職前教師教學能力檢定評分量表」包含「教學設計」、「教學方法與技巧」、「教學媒材與溝通」、「以及班級經營與師生互動」四個向度，二十項指標；同時建立二十項指標五個等第的評分規準，提供評分的參照依據；最後，說明評分量表的運用方式，以利相關人員使用。本評分量表可適用於師資培育機構檢定職前教師教學能力之標準，或作為形成性評量工具，協助職前教師改善自身的教學能力；亦可作為教育機構甄選教師時試教之評分工具。 This study was conducted to develop a rating scale for assessing the teaching competency of elementary school preservice teachers at the Department of Education, National Hsinchu University of Education, Taiwan. In this study, the rating scale was designed using questionnaires that were developed through applying the Delphi method. Delphi data analysis was conducted by 17 experts over 3 rounds, after which adjustments were made to improve the rating scale. Subsequently, preservice teachers into the fourth year of their study were recruited to test the rating scale. Two tests were conducted, each involving 8 preservice teachers and 3 rating staff, and the scores for the 2 rating tests were collected for analysis. Interrater reliability was tested using the Kendall's W harmonic coefficient test, and the preservice teachers and rating staff were interviewed to revise the rating scale indicators. The rating scale proposed in this study comprised 4 dimensions (i.e., instructional design, teaching methods and techniques, teaching media and communication, and classroom management and teacher-student interactions) and 20 indicators. A 5-level assessment rubric was formulated to rate the 20 indicators. Finally, method of using the rating scale was outlined in the paper for related personnel to use the scale correctly. The proposed rating scale can be used by teacher education institutions to assess the teaching competency of preservice teachers. In addition, the scale can be used as formative assessment instruments to assist preservice teachers in improving their teaching competency, or as an evaluation instrument for education institutions hiring teachers.